2015
DOI: 10.1088/2053-1583/2/4/044012
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependence of superconductivity and superconductor–insulator transition in ultrathin FeSe films on SrTiO 3 (001) substrate

Abstract: Interface-enhanced high-temperature superconductivity in one unit-cell (UC) FeSe film on SrTiO 3 (001) (STO) substrate has recently attracted much attention in condensed matter physics and material science. Here, by ex situ transport measurements, we report on the superconductivity in FeSe ultra-thin films with different thickness on STO substrate. We find that the onset superconducting transition temperature (T c ) decreases with increasing film thickness of FeSe, which is opposite to the behavior usually obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 53 publications
6
33
0
1
Order By: Relevance
“…The opposite behaviour seen here reflects the decaying influence from the substrate. Previous transport measurements have revealed that thicker FeSe films on SrTiO3 also exhibit lower transition temperatures as well as wider transition temperature regions, suggesting that only the first UC of FeSe at the interface is superconducting [35,39]. The same thickness dependence seen in FeSe/NdGaO3(110) system, therefore, indicates here also only the first UC FeSe becomes superconducting.…”
Section: Resultssupporting
confidence: 64%
“…The opposite behaviour seen here reflects the decaying influence from the substrate. Previous transport measurements have revealed that thicker FeSe films on SrTiO3 also exhibit lower transition temperatures as well as wider transition temperature regions, suggesting that only the first UC of FeSe at the interface is superconducting [35,39]. The same thickness dependence seen in FeSe/NdGaO3(110) system, therefore, indicates here also only the first UC FeSe becomes superconducting.…”
Section: Resultssupporting
confidence: 64%
“…Similarly, the predominance of hole-type carriers in PLD-grown multilayer FeSe thin films grown on CaF 2 substrates was also verified by angle-resolved photoemission spectroscopy (ARPES) measurements by Shen et al [73]. In other words, the enhanced T c in #FT-300 could be excluded from the heavily electron-doped HTS scenarios [25,30,44,47,65,66]. In addition, the temperature dependence of the normalized resistance [y axes in Figs.…”
Section: Resultsmentioning
confidence: 72%
“…For example, an alkali-metalcoating (Li, K) process [38][39][40][41][42][43] was found promising for introducing massive electron doping into multilayer FeSe films on STO. Wang et al [44] reported that a postannealing procedure is another effective way to introduce electron charge carriers into a multilayer FeSe system and realize an insulatorsuperconductor transition. A novel method was also proposed by Shiogai et al [45,46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, systematic investigations on the bosonic excitation mode remain scarce [13] in the recently discovered one-unit-cell (1-UC) FeSe on SrTiO 3 (001) (STO) [14]. The 1-UC FeSe/STO grown by molecular-beam epitaxy (MBE), which ranks the highest critical temperature (T c ) (typically 65 K) in iron-based superconductors, has triggered tremendous research interest in condensed-matter physics [15][16][17][18][19][20][21][22][23]. Photoemission spectroscopy suggests that the Fermi surface consists of only electron pockets at M points [15], different from that found in bulk FeSe and iron pnictides with additional hole pockets at Γ point.…”
mentioning
confidence: 99%